Vascular Behçet syndrome: from pathogenesis to treatment - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (My University, 2022)
© 2022, Springer Nature Limited.Behçet syndrome is a rare, chronic inflammatory disease of unknown aetiopathogenesis, most commonly presenting with mucocutaneous and ocular manifestations. Vascular involvement, most frequently superficial vein and deep vein thrombosis, can occur in up to 50% of patients with Behçet syndrome. Venous thrombosis at atypical sites (inferior and superior vena cava, suprahepatic veins with Budd–Chiari syndrome, portal vein, cerebral sinuses and right atrium and/or ventricle) and arterial involvement (mostly in situ thrombosis and aneurysms of the pulmonary arteries, as well as aneurysms of the abdominal aorta, and peripheral and visceral arteries) are also unique features of Behçet syndrome. Behçet syndrome is considered a natural model of inflammation-induced thrombosis in humans, with an impaired immune-inflammatory response rather than traditional cardiovascular risk factors contributing to thrombogenesis. Specifically, neutrophil hyperactivation and neutrophil-mediated mechanisms of damage directly promote endothelial dysfunction, platelet activation and thrombogenesis in Behçet syndrome. This unusual pathogenesis directly determines the treatment approach, which relies mostly on immunosuppressants rather than anticoagulants for treatment of thrombosis and for secondary prevention. This Review discusses the main histopathological, pathogenetic and clinical aspects of vascular Behçet syndrome, addressing their implications for therapeutic management. Future perspectives in terms of pathogenetic studies, disease monitoring and treatment strategies are also discussed.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ROMATOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; RHEUMATOLOGY; Romatoloji; Rheumatology